Pain assessment in unconscious patients in the intensive care unit - Kunigėlytė, Indrė; Paulikienė, Simona (Slauga. Mokslas ir praktika, 2020)
Many patients can experience significant pain in the Intensive Care Unit (ICU). Unconscious patients’ pain can be untreated or treated inadequately because they are incapable to express it by words. Nurses are in close contact with their patients, therefore they need to be able to evaluate their pain using adequate methods, do it frequently and when it’s necessary.The aim of this study was to analyze pain assessment in unconscious patients in the Intensive Care Unit. To reach this goal, nurses’ pain assessment tendencies were assessed, nurses’ valued signs in unconscious patients which for them represented pain were identified and compared with indicators in standardized pain assessment tools - the Critical-Care Pain Observation Tool (CPOT) and the Behavioral Pain Scale (BPS). The study was conducted in several Intensive Care Units at Vilnius city clinical hospital. Data was collected from 41 critical care nurses who filed out questionnaire composed by the authors of this study. To verify the results, 8 nurses’ pain assessment in unconscious patients were observed and logged in observation sheet. Obtained data showed that majority nurses evaluate unconscious patients’ pain only during procedures. The main pain indicators nurses focus on are changes in facial expressions (fully tightened, grimacing), vocalization (sighing, moaning, crying out) and changes in patients’ heart rate (tachycardia). The most commonly used indicators by nurses to identify pain in unconscious patients partially coincided with standardize pain assessment tools’ indicators.
Keywords: unconscious patients; pain; assessment; intensive care